2017
DOI: 10.1186/s13620-016-0080-7
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Pasteurella multocida among pigs with respiratory disease in China between 2011 and 2015

Abstract: BackgroundPrior to the 1990s, P. multocida capsular serogroup A was the most prevalent in China, followed by serogroups B and D. Thirty years later, serogroup D became the most prevalent, followed by serogroups A and B. However, the P. multocida capsular serogroups currently circulating in China remain unclear. Therefore, the aim of the present study was to provide an update on P. multocida serogroups isolated from diagnostic samples collected from clinically diseased pigs in Central and Eastern China from 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 26 publications
2
22
1
Order By: Relevance
“…The predominate capsule: LPS genotypes defined among the porcine isolates were types D: L6 (42.86%), A: L3 (25.00%), and A: L6 (23.21%). Those are because P. multocida strains with porcine pasteurellosis are frequently designated capsular types A and D (Tang et al, 2009 ; Liu et al, 2017 ; Peng et al, 2018 ), and LPS serovars 3, 4, and 12 (Pijoan et al, 1983 ; Lainson et al, 2002 ; Jamaludin et al, 2005 ). In particular, these results are in agreement with the latest molecular epidemical data in China (Peng et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The predominate capsule: LPS genotypes defined among the porcine isolates were types D: L6 (42.86%), A: L3 (25.00%), and A: L6 (23.21%). Those are because P. multocida strains with porcine pasteurellosis are frequently designated capsular types A and D (Tang et al, 2009 ; Liu et al, 2017 ; Peng et al, 2018 ), and LPS serovars 3, 4, and 12 (Pijoan et al, 1983 ; Lainson et al, 2002 ; Jamaludin et al, 2005 ). In particular, these results are in agreement with the latest molecular epidemical data in China (Peng et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another genus, Pasteurella , was relatively abundant in the diseased groups from the two farms, even though no statistical significance was observed ( p > 0.05). P. multocida is an opportunistic pathogen and a common inhabitant of the upper respiratory tract of many animals, and a causative agent of numerous important diseases, including respiratory diseases (Hansen et al, 2010; Liu et al, 2017). In addition, a high prevalence of P. multocid a was demonstrated from cases of porcine bronchopneumonia, which was considered a secondary pathogen, dependent on co-infections or immunosuppression of the host (Pors et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…P. multocide along with the Bordetella bronchiseptica causes acute atrophic rhinitis to pig related to high strain toxigenicity, because the P. multocide play a dominant role leading to the development of anthropic rhinitis lesi (Magyar et al 2013;Kubatzky 2012;Shayegh et al 2009) as well as it is related to pneumonia and septicemia diseases (De Oliveira et al 2015). Liu et al (2017) reported that prevalence of P. multocide Serotype A is the most common in China before 1990 followed by serotype B and D.…”
Section: Introductionmentioning
confidence: 99%